Pathways to Deep Decarbonization in Italy - Isabella Alloisio; Alessandro Antimiani; Simone Borghesi; Enrica De Cian; Maria Gaeta; Chiara Martini; Ramiro Parrado; Maria Cristina Tommasino; Elena Verdolini; Maria Rosa Virdis (Fondazione Eni Enrico Mattei (FEEM), 2015)
The Deep Decarbonization Pathways Project (DDPP), an initiative of the Sustainable Development Solutions Network (SDSN) and the Institute for Sustainable Development and International Relations (IDDRI), aims to demonstrate how countries can transform their energy systems by 2050 in order to achieve a low-carbon economy and significantly reduce the global risk of catastrophic climate change. Built upon a rigorous accounting of national circumstances, the DDPP defines transparent pathways supporting the decarbonization of energy systems while respecting the specifics of national political economy and the fulfillment of domestic development priorities. The project comprises 16 Country Research Teams, composed of leading research institutions from countries representing about 70% of global GHG emissions and at very different stages of development. These 16 countries are: Australia, Brazil, Canada, China, France, Germany, India, Indonesia, Italy, Japan, Mexico, Russia, South Africa, South Korea, the United Kingdom, and the United States. “Pathways to Deep Carbonization in Italy” contributes to the national debate on climate-change mitigation, and the importance of deep decarbonization, by examining three alternative pathways that could reduce Italian CO2 emissions by at least 40% in 2030 and 80% in 2050, compared to 1990. It analyzes the challenges the Italian energy system faces, and possible future technological developments that will need to be pursued.
Keywords: Q4; Q5; 330; Decarbonization; Low-carbon Economy; Climate Change